Rationality of Extension of Term of Office of Notary Public - Jannah, Roudlatul; Alfath, Tahegga Primananda (Journal of Law, Politic and Humanities, 2025)
The retirement age for the position of Notary, as stipulated in Article 8 paragraph (1) letter b and Article 8 paragraph (2) of Law No. 30 of 2004 on the Position of Notary, explicitly limits the maximum age for holding the position to 65 (sixty-five) years. However, an extension may be granted up to 67 (sixty-seven) years. The Constitutional Court considers this retirement age regulation to be "constitutional," thereby opening the possibility for Notaries to extend their tenure until the age of 70 (seventy), provided they undergo a medical examination at a government hospital or a hospital designated by the Minister of Law. Following Constitutional Court Decision No. 84/PUU-XXII/2024, which allows Notaries to serve until the age of 70, this article explores the reasons behind the extension and the legal procedures required for its implementation.